2003
DOI: 10.1177/0020764003494005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Community Mental Health in Developing Societies: Evaluation of a Checklist Format in Nepal

Abstract: The first step in obtaining high quality information on the distribution of mental illness in developing countries is to establish some reliable and valid indicators of disorder. The checklist format for assessing disorder appears to meet this objective and offers the possibility that community-level prevalence studies can be reasonably conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Other investigators have suggested that somatization symptoms (rather than specific symptomatic complaints) are an expression of depression and anxiety in Latino and Asian populations (Canino, 2004;Pina & Silverman, 2004;Varela et al, 2004). In addition, the CIDI is somewhat difficult to administer in community settings with high rates of low literacy and inexperience in responding to surveys because of its complex wording (Tausig, Subedi, & Broughton, 2003).Given these factors, response biases in reports of psychopathology may be influenced by longer U.S. residence, due to greater exposure to symptom terminology used in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have suggested that somatization symptoms (rather than specific symptomatic complaints) are an expression of depression and anxiety in Latino and Asian populations (Canino, 2004;Pina & Silverman, 2004;Varela et al, 2004). In addition, the CIDI is somewhat difficult to administer in community settings with high rates of low literacy and inexperience in responding to surveys because of its complex wording (Tausig, Subedi, & Broughton, 2003).Given these factors, response biases in reports of psychopathology may be influenced by longer U.S. residence, due to greater exposure to symptom terminology used in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…The most time and resource consuming approach to developing a comprehensive psychiatric instrument for Nepal would be to develop a novel instrument. One study did not go quite this far but instead used the DSM‐III checklist of symptoms directly as a screening tool as described above (Tausig et al ., ). This study did not employ an expert panel to confirm the validity of their translation.…”
Section: Discussionmentioning
confidence: 97%
“…Tausig et al . () created a novel instrument based on a modified version of the DSM III symptom checklist. They translated the individual checklist items into Nepali in the categories of somatization, anxiety, depression, mania, schizophrenia and antisocial personality disorder and administered these questions door‐to‐door to a random sample of 653 people in Jirel, Nepal (van Ommeren et al ., ).…”
Section: Psychiatric Scales Used In Nepalmentioning
confidence: 99%
“…The DSM-III-R Checklist contains symptom lists for 21 disorders; however, using the entire checklist would have made the survey too lengthy for the target population. The reliability and validity of the instrument used in this study have been examined in considerable detail and have been shown to be acceptable (Tausig et al, 2003). The diagnoses of depression and anxiety have the highest reliability as indices, whereas the diagnosis of antisocial personality disorder is subject to considerable uncertainty (no data for antisocial personality disorder will be reported).…”
Section: The Dsm-iii-r Criteria Checklistmentioning
confidence: 97%